Acute painful paraplegia in a 49-year-old man with allergic asthma. (30th June 2014) - Sorino, Claudio; Agati, Sergio; Milani, Giuseppe; Maspero, Annarosa
Abstract : We present a case of a 49-year-old man, with a 10-year history of bronchial asthma and nasal polyposis, who developed acutely painful paraplegia and paresthesias. Laboratory data showed elevated blood creatine kinase levels and myoglobinuria, which were diagnostic for rhabdomyolysis but only partially explained the neurological deficit. Electrophysiological studies revealed a sensorimotor neuropathy of multiple mononeuritis type. The patient also had leucocytosis with marked eosinophilia and antineutrophil cytoplasmic autoantibodies. Bronchial biopsies showed inflammatory infiltrates with a prevalence of eosinophils. All these findings led us to diagnose eosinophilic granulomatosis with polyangiitis, a systemic vasculitis with almost constant respiratory tract involvement and good response to corticosteroid treatment. This can also affect other organs including the nervous system, while muscular involvement is unusual. Some diseases deserve attention in differential diagnosis. Histology can support the diagnosis which remains essentially clinical. Steroid sparing agents/immunosuppressants are suggested for extensive disease.